Tax Reform dan Kendalanya - Budi Santoso Handoyo (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Attempt of taxation reform in Indonesia can be said to have occurred twice. The first reform tookplace in 1983, and constituted an extraordinary reform inasmuchas it update all Dutch-colonial inheritance taxation system. Ten years later, the second tax reform occurred, and it attempted to perfect the tax laws and regulations which had existed since1983. This was due to the occurrence of perfection in all aspects of taxation laws and regulationsincluding KUP, PPN, PPH, and PPB. However, to execute all results of the aforementioned reform is difficult. Various abstracles to implement a taxation system after the effectiveness of the taxation reforms can be found. Indeed, a strong and good will is required to settle those barriers. Thus, Indonesia can be developed on the basis offunding resulting from taxes.